MARGINALITAS PEREMPUAN DALAM KAKAWIN RAMAYANA: ANALISIS WACANA KRITIS - Ari Dwijayanthi, Ni Made (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Kakawin Ramayana is one of Old Javanese poetry. Sita is the central female character in the Kakawin Ramayana. Her position as a woman was marginalized when her chastity was doubted by her husband Rama. Masatya (plunging into the fire) was used as a way for Sita to proved to Rama that she was holy. Phenomenon of masatya in the Kakawin Ramayana was researched using qualitative methods and analyzed using Fairclough's Critical Discourse Theory which includes: text dimensions (microstructural), discourse practice (mesostructural), and sociocultural practice (macrostructural).